Multistage fireproof nano-composite building material and preparation method thereof
Through multi-layer structure multi-stage fire-resistant nanocomposite building materials, combined with basic nanomaterials and fire-resistance enhancers, the existing fire-resistant building materials have been solved, and the problems of large weight, easy cracking and limited fire-resistance grades have been achieved, efficient fire-proof and thermal insulation effect and lightweight mechanical properties have been achieved, which reduces the preparation cost and meets environmental protection requirements.
Patent Information
- Application Number
- CN202411902910.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fire-proof building materials have problems such as large weight, easy cracking, and limited fire protection grade, which is difficult to meet the needs of high-rise buildings and places with high fire protection requirements. At the same time, the preparation method is complex and the cost is high.
Multi-stage fire-resistant nanocomposite building materials with multi-layer structures are used, and the raw materials components of the core layer include basic nanomaterials, fire-resistance enhancers and binders. Through high-speed dispersion treatment and multi-layer structure construction technology, an efficient fire-resistant and heat-insulating layer is formed.
It significantly improves the fire resistance of building materials, can effectively prevent the spread of fire, optimizes the mechanical properties, achieves lightweight and aesthetics, and reduces the preparation cost and meets environmental protection requirements.
Smart Images

Figure CN119704845A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano building materials, and specifically discloses a multi-level fireproof nano composite building material and a preparation method thereof. Background Art
[0002] With the rapid development of the modern construction industry, people have put forward higher and higher requirements on the safety performance, aesthetics and practicality of building materials. As an important part of ensuring building safety, the research and development and application of fireproof building materials are particularly important. Although traditional fireproof building materials, such as gypsum board and mineral wool board, can meet the fire protection needs to a certain extent, they often have many limitations. For example, these materials are usually heavy, which increases the load on the building; they are easy to crack, affecting the appearance and service life; the fire protection level is limited, and it is difficult to cope with the threat of high-intensity fires. Therefore, the development of new fireproof building materials to overcome the shortcomings of traditional materials has become an urgent problem to be solved in the construction industry.
[0003] In recent years, the rise of nanotechnology has injected new vitality into the innovation of fireproof building materials. Nanomaterials have shown unprecedented potential in the field of fire protection due to their unique physical and chemical properties. Through nano-level design and regulation, the fire resistance of materials can be significantly improved, such as improving the high temperature resistance, flame retardancy and thermal insulation performance of materials. At the same time, nanomaterials also have the characteristics of light weight, high strength and easy processing, which helps to achieve lightweight, high strength and aesthetics of building materials.
[0004] However, despite the many advantages of nano-fireproof building materials, the products currently on the market still have some shortcomings. First, the core layer raw material components of some nano-fireproof building materials are relatively single, resulting in limited fireproof performance, which is difficult to meet the needs of high-rise buildings, large public facilities and other places with high fire protection requirements. Secondly, the preparation methods of some nano-fireproof building materials are complicated and costly, making it difficult to achieve large-scale promotion and application. In addition, for the surface treatment of building materials, traditional fire-retardant coatings often have problems such as poor adhesion to the substrate, easy to fall off, and low fire protection level, which seriously affects the overall fireproof effect and service life of the building materials.
[0005] In summary, it is particularly urgent to develop a new type of multi-level fire-resistant nano-composite building material. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a multi-level fireproof nano-composite building material and a preparation method thereof.
[0007] The present invention includes the following technical solutions:
[0008] A multi-level fireproof nano-composite building material, characterized by core layer raw material components, structure and preparation method, including:
[0009] (I) Core layer raw material components:
[0010] (a) basic nanomaterial: at least one inorganic nanoparticle selected from nano-silicon dioxide, nano-aluminum oxide, nano-zirconium oxide, nano-calcium carbonate or nano-carbon material, used to provide basic strength and fire resistance of building materials;
[0011] (b) Fire-proof enhancer: comprising nano-scale intumescent flame retardant, nano-scale aluminum hydroxide, nano-scale magnesium hydroxide or a combination thereof, which is used to release moisture and gas in a fire to form a heat-insulating layer to prevent the spread of fire;
[0012] (c) Binders and additives: Use polymer resins, nanoclays, dispersants, coupling agents and plasticizers to improve the bonding strength and processing performance between raw materials;
[0013] (II) Building material structure:
[0014] This building material is designed as a multi-layer structure, including:
[0015] (1) Surface layer: covered by nano-scale fire retardant coating, providing initial fire protection and aesthetic effect;
[0016] (2) a plurality of core layers: a nanocomposite material prepared by mixing the raw material components in (i) above as the core layer;
[0017] (3) Several isolation layers: located between the core layers or between the core layer and the surface layer, made of nanoporous materials, used to isolate heat transfer and flame penetration;
[0018] (III) Preparation method:
[0019] Step 1: Preparation and pretreatment of core layer raw materials: Mix the basic nanomaterials, fire retardant enhancers, binders and additives in proportion and perform high-speed dispersion treatment to ensure that each component is evenly dispersed;
[0020] Step 2: Core layer preparation: The pre-treated mixture is subjected to processes such as extrusion, injection molding or compression molding to form a preliminary core layer sheet;
[0021] Step 3: Multi-layer structure construction: According to the design requirements, the core layer panels are stacked, and the isolation layer materials are added between the layers. The layers are tightly combined through hot pressing or vacuum pressing technology;
[0022] Step 4: Surface treatment: spraying nano-level fire-retardant coating on the surface of the building material to produce the multi-level fire-retardant nano-composite building material.
[0023] Furthermore, in the above-mentioned multi-level fireproof nano-composite building material, the basic nano-material in the core layer raw material component is a mixture of nano-silicon dioxide and nano-alumina, the nano-silicon dioxide particle size is 10-30 nanometers, the nano-alumina particle size is 20-60 nanometers, and the weight ratio is 1:1.5 to 1:2.5.
[0024] Furthermore, in the above-mentioned multi-level fireproof nano-composite building material, the fireproof enhancer in the core layer raw material component is a mixture of nano-scale intumescent flame retardant and nano-scale aluminum hydroxide, the particle size of which is less than 100 nanometers, and the weight ratio is 1:0.8 to 1:1.2.
[0025] Furthermore, in the above-mentioned multi-level fireproof nano-composite building material, the core layer raw material components include:
[0026] The polymer resin is epoxy resin or polyurethane resin, with a molecular weight of 2000-6000 and an addition amount of 10%-20%;
[0027] The particle size of nanoclay is less than 50 nanometers, and the addition amount is 2%-5%;
[0028] The dispersant is polycarboxylate, added in an amount of 0.5%-1.5%;
[0029] The coupling agent is silane or titanate, and the addition amount is 0.5%-1.5%;
[0030] The plasticizer is phthalate ester, and the added amount is 1%-3%.
[0031] Furthermore, in the step 1 of the preparation method of the multi-level fireproof nanocomposite building material:
[0032] The high-speed dispersion processing speed is 3000-4000 rpm, the processing time is 20-25 minutes, and it is supplemented by ultrasonic dispersion.
[0033] Furthermore, in the step 2 of the preparation method of the multi-level fireproof nanocomposite building material:
[0034] The molding process temperature is 150-170 degrees Celsius, the pressure is 10-15MPa, and it is naturally cooled to room temperature.
[0035] Furthermore, in step 3 of the above-mentioned method for preparing multi-stage fireproof nanocomposite building materials:
[0036] The hot pressing or vacuum pressing temperature is 130-160 degrees Celsius, the pressure is 8-15MPa, and the holding time is 20-25 minutes.
[0037] Furthermore, in the step 4 of the preparation method of the multi-level fireproof nanocomposite building material:
[0038] The selected fire retardant coating is sprayed with a thickness of 80-150 microns, sprayed and dried at least three times, and cooled naturally after each spraying.
[0039] Furthermore, in the isolation layer of the multi-level fireproof nanocomposite building material structure:
[0040] The nanoporous material is nano-scale silica aerogel or nano-carbon foam, with a porosity of not less than 92%, a thermal conductivity of less than 0.015 W / (m·K), and a thickness of 2-4 mm.
[0041] Furthermore, the fire retardant coating used on the surface of the multi-level fireproof nano-composite building material is:
[0042] Selected from acrylic fire retardant coating, epoxy resin fire retardant coating or polyurethane fire retardant coating, and its fire protection grade is not lower than B1 grade.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The multi-stage fireproof nano-composite building material of the present invention, by cleverly combining a variety of basic nano-materials and fireproofing enhancers, constructs a multi-layer fireproof structure, significantly improves the fireproof performance of the building material, can effectively prevent the spread of fire, and provides a strong guarantee for building safety. At the same time, the introduction of nano-materials not only optimizes the mechanical properties of the building materials and achieves lightweight, but also enhances the aesthetics and durability of the building materials through the nano-scale fireproof coating on the surface, ensuring the stability of long-term use. In addition, the preparation method of the present invention is simple and efficient, cost-controlled, easy to achieve large-scale production, and the selected materials meet environmental protection requirements, reducing the impact on the environment. In summary, the multi-stage fireproof nano-composite building material of the present invention shows significant advantages in terms of fireproof performance, mechanical properties, preparation process and environmental sustainability, bringing a new choice of high-performance, safe and reliable, economical and environmentally friendly fireproof building materials to the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Comparison of mechanical strength of building materials of Examples 1-3;
[0046] Figure 2 Mechanical strength of the building materials of Example 3 and Comparative Examples 1-3;
[0047] Figure 3 The heat insulation capacity (m 2 ·K / W). DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Embodiment 1:
[0050] A multi-level fireproof nano composite building material, which is specifically prepared as follows:
[0051] Core layer raw material components:
[0052] Basic nanomaterial: a mixture of nano-silicon dioxide (particle size 20nm) and nano-alumina (particle size 40nm), with a weight ratio of 1:2.
[0053] Fireproof enhancer: a mixture of nano-scale intumescent flame retardant (particle size <100nm) and nano-scale aluminum hydroxide (particle size <100nm), with a weight ratio of 1:1 and an addition amount of 10%;
[0054] Binder and additives: epoxy resin (molecular weight 4000), added in an amount of 15%; nano clay (particle size <50nm), added in an amount of 3%; polycarboxylate dispersant, added in an amount of 1%; silane coupling agent, added in an amount of 1%; phthalate plasticizer, added in an amount of 2%.
[0055] The added amount is based on 100% of the basic nanomaterial.
[0056] Building material structure:
[0057] Surface: Acrylic fire retardant paint, fire rating B1, spray thickness 100 microns.
[0058] Core layer: three layers, each layer is made by mixing the above raw material components, and each layer is 10 mm thick.
[0059] Isolation layer: Located between the core layers, it uses nano-scale silica aerogel with a porosity of 94%, a thermal conductivity of 0.012 W / (m·K), and a thickness of 3 mm.
[0060] Preparation method:
[0061] Preparation and pretreatment of core layer raw materials: Mix the components in proportion, use a high-speed disperser to process at 3500 rpm for 20 minutes, and assist with ultrasonic dispersion.
[0062] Core layer preparation: The pretreated mixture was injection molded at 160 degrees Celsius and 12 MPa, and naturally cooled to room temperature.
[0063] Multi-layer structure construction: Three core layer panels are stacked, and isolation layer materials are added between the layers. Hot pressing is maintained at 140 degrees Celsius and 10MPa for 20 minutes to make the layers tightly bonded.
[0064] Surface treatment: Spray acrylic fire retardant paint on the surface of building materials three times, cool naturally after each spraying, and the total spraying thickness is 100 microns.
[0065] Example 2
[0066] A multi-level fireproof nano composite building material, which is specifically prepared as follows:
[0067] Core layer raw material components:
[0068] Basic nanomaterial: a mixture of nano-silicon dioxide (particle size 15nm) and nano-aluminum oxide (particle size 30nm), with a weight ratio of 1:1.5.
[0069] Fireproof enhancer: a mixture of nano-scale intumescent flame retardant (particle size <90nm) and nano-scale magnesium hydroxide (particle size <90nm), with a weight ratio of 1:0.8 and an addition amount of 10%.
[0070] Binder and additives: polyurethane resin (molecular weight 3000), added in an amount of 20%; nano clay (particle size <40nm), added in an amount of 5%; polycarboxylate dispersant, added in an amount of 1.5%; titanate coupling agent, added in an amount of 1.5%; phthalate plasticizer, added in an amount of 3%.
[0071] The added amount is based on 100% of the basic nanomaterial.
[0072] Building material structure:
[0073] Surface: Epoxy resin fire retardant coating, fire rating B1, spray thickness 120 microns.
[0074] Core layer: four layers, each layer is made by mixing the above raw material components, and each layer is 10 mm thick.
[0075] Isolation layer: located between the core layer and the surface layer, made of nano-carbon foam, with a porosity of 95%, a thermal conductivity of 0.010 W / (m·K), and a thickness of 3 mm.
[0076] Preparation method:
[0077] Preparation and pretreatment of core layer raw materials: Mix the components in proportion, use a high-speed disperser to process at 4000 rpm for 25 minutes, and assist with ultrasonic dispersion.
[0078] Core layer preparation: The pretreated mixture was pressed into shape at 170 degrees Celsius and 15 MPa, and naturally cooled to room temperature.
[0079] Multi-layer structure construction: Four core layer panels are stacked, and the isolation layer material is added to the top layer. Vacuum pressing is maintained at 150 degrees Celsius and 15MPa for 25 minutes to make the layers tightly bonded.
[0080] Surface treatment: Spray epoxy resin fire retardant paint three times on the surface of building materials, cool naturally after each spraying, and the total spraying thickness is 100 microns.
[0081] Example 3
[0082] A multi-level fireproof nano composite building material, which is specifically prepared as follows:
[0083] Core layer raw material components:
[0084] Basic nanomaterial: a mixture of nano zirconium oxide (particle size <50nm) and nano calcium carbonate (particle size <30nm), with a weight ratio of 1:2.5.
[0085] Fire retardant enhancer: a mixture of nano-aluminum hydroxide (particle size <80nm) and nano-magnesium hydroxide (particle size <80nm), with a weight ratio of 1:1.2 and an addition amount of 10%.
[0086] Binder and additives: epoxy resin (molecular weight 6000), added in an amount of 10%; nano clay (particle size <30nm), added in an amount of 2%; polycarboxylate dispersant, added in an amount of 0.5%; silane coupling agent, added in an amount of 0.5%; phthalate plasticizer, added in an amount of 1%.
[0087] The added amount is based on 100% of the basic nanomaterial.
[0088] Building material structure:
[0089] Surface: Polyurethane fire retardant coating, fire rating B1, spray thickness 150 microns.
[0090] Core layer: five layers, each layer is made by mixing the above raw material components, and each layer is 10 mm thick.
[0091] Isolation layer: located between every two core layers, using nano-scale silica aerogel, with a porosity of 92%, a thermal conductivity of 0.015W / (m·K), and a thickness of 3 mm.
[0092] Preparation method:
[0093] Preparation and pretreatment of core layer raw materials: Mix the components in proportion, use a high-speed disperser to process at 3000 rpm for 22 minutes, and assist with ultrasonic dispersion.
[0094] Core layer preparation: The pretreated mixture was extruded at 150 degrees Celsius and 10 MPa and naturally cooled to room temperature.
[0095] Multi-layer structure construction: Five layers of core layer panels are stacked, and isolation layer materials are added between each layer. Hot pressing is maintained at 130 degrees Celsius and 8MPa for 22 minutes to make the layers tightly bonded.
[0096] Surface treatment: Spray polyurethane fire retardant coating on the surface of building materials three times, cool naturally after each spraying, and the total spraying thickness is 100 microns.
[0097] Comparative Example 1
[0098] A multi-level fireproof nano composite building material, which is specifically prepared as follows:
[0099] Core layer raw material components:
[0100] Basic nanomaterial: a mixture of nano zirconium oxide (particle size <50nm) and nano calcium carbonate (particle size <30nm), with a weight ratio of 1:2.5.
[0101] Fire retardant enhancer: a mixture of nano-aluminum hydroxide (particle size <80nm) and nano-magnesium hydroxide (particle size <80nm), with a weight ratio of 1:1.2 and an addition amount of 10%.
[0102] Binder and additives: epoxy resin (molecular weight 6000), added in an amount of 10%; nano clay (particle size <30nm), added in an amount of 2%; polycarboxylate dispersant, added in an amount of 0.5%; silane coupling agent, added in an amount of 0.5%; phthalate plasticizer, added in an amount of 1%.
[0103] The added amount is based on 100% of the basic nanomaterial.
[0104] Building material structure:
[0105] Surface: Polyurethane fire retardant coating, fire rating B1, spray thickness 150 microns.
[0106] Core layer: five layers, each layer is made by mixing the above raw material components, and each layer is 10 mm thick.
[0107] Isolation layer: located between every two core layers, using nano-scale silica aerogel, with a porosity of 92%, a thermal conductivity of 0.015W / (m·K), and a thickness of 3 mm.
[0108] Preparation method:
[0109] Preparation and pretreatment of core layer raw materials: Mix the components in proportion, use a high-speed disperser to process at 3000 rpm for 22 minutes, and assist with ultrasonic dispersion.
[0110] Core layer preparation: The pretreated mixture was extruded at 150 degrees Celsius and 10 MPa and naturally cooled to room temperature.
[0111] Multi-layer structure construction: Five layers of core layer panels are stacked, and isolation layer materials are added between each layer. Hot pressing is maintained at 130 degrees Celsius and 8MPa for 22 minutes to make the layers tightly bonded.
[0112] Surface treatment: Spray polyurethane fire retardant coating on the surface of building materials three times, cool naturally after each spraying, and the total spraying thickness is 100 microns.
[0113] The difference between Comparative Example 1 and Example 3 is that the basic nano material does not contain nano zirconium oxide, and the rest is the same.
[0114] Comparative Example 2
[0115] The fireproof reinforcing agent does not contain nano-aluminum hydroxide, and the rest is the same as in Example 3.
[0116] Comparative Example 3
[0117] No isolation layer is included, and the rest is the same as in Example 3.
[0118] Test Case
[0119] 1. Test the mechanical strength of the building materials of Examples 1-3.
[0120] Table 1 Mechanical strength of building materials of Examples 1-3
[0121]
[0122] It can be seen from the data in Table 1 that the multi-level fireproof nano-composite building material of the present invention has high mechanical strength and is very suitable for use as a building material.
[0123] The mechanical strength of Example 3 and Comparative Examples 1-3 were tested.
[0124] Table 2 Mechanical strength of building materials of Example 3 and Comparative Examples 1-3
[0125]
[0126] From the data in Table 1, it can be seen that adding an isolation layer can increase the compressive strength and flexural strength to a certain extent.
[0127] 2. Fireproof and heat insulation performance test.
[0128] The fireproof and heat-insulating properties of Example 2 and Comparative Examples 1-3 were tested.
[0129] The flame retardant properties of materials are determined according to the "Classification of Combustion Performance of Building Materials and Products" (GB8624-2012). Using the guarded hot plate method: Determine the steady-state heat transfer properties of 100mm thick insulation materials, and determine its thermal resistance m according to the standard GB / T10294-2008. 2 ·K / W. The results are shown in Table 3
[0130] Table 3 Fireproof and heat insulation performance of Example 2 and Comparative Examples 1-3
[0131] serial number Flame retardant properties <![CDATA[Thermal insulation ability (m 2 ·K / W) <!-- 6 -->]]> Example 3 A 4.37 Comparative Example 1 A 3.78 Comparative Example 2 B1 2.79 Comparative Example 3 B1 2.12
[0132] From the comparison between Example 3 and Comparative Examples 1-3, it can be seen that the use of an isolation layer can greatly improve the flame retardancy and heat insulation capabilities of the material of the present invention, while the addition of nano zirconium oxide and nano-aluminum hydroxide can also synergistically increase the flame retardancy and heat insulation capabilities.
[0133] As can be seen from the above embodiments, the multi-stage fireproof nano composite building materials of the present invention, by cleverly combining a variety of basic nano materials and fireproof reinforcing agents, construct a multi-layer fireproof structure, significantly improve the fireproof performance of building materials, can effectively prevent the spread of fire, and provide a strong guarantee for building safety. At the same time, the introduction of nano materials not only optimizes the mechanical properties of building materials and achieves lightweight, but also enhances the aesthetics and durability of building materials through the nano-scale fireproof coating on the surface, ensuring the stability of long-term use. In addition, the preparation method of the present invention is simple and efficient, cost-controlled, easy to achieve large-scale production, and the selected materials meet environmental protection requirements, reducing the impact on the environment. In summary, the multi-stage fireproof nano composite building materials of the present invention show significant advantages in fireproof performance, mechanical properties, preparation process and environmental sustainability, bringing a new choice of high-performance, safe and reliable, economical and environmentally friendly fireproof building materials to the construction industry.
[0134] The above are limited to several preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A multi-level fireproof nanocomposite building material, characterized in that The core layer raw material components, structure and preparation method include: (I) Core layer raw material components: (a) basic nanomaterial: at least one inorganic nanoparticle selected from nano-silicon dioxide, nano-aluminum oxide, nano-zirconium oxide, nano-calcium carbonate or nano-carbon material, used to provide basic strength and fire resistance of building materials; (b) Fire-proof enhancer: comprising nano-scale intumescent flame retardant, nano-scale aluminum hydroxide, nano-scale magnesium hydroxide or a combination thereof, which is used to release moisture and gas in a fire to form a heat-insulating layer to prevent the spread of fire; (c) Binders and additives: Use polymer resins, nanoclays, dispersants, coupling agents and plasticizers to improve the bonding strength and processing performance between raw materials; (II) Building material structure: This building material is designed as a multi-layer structure, including: (1) Surface layer: covered by nano-scale fire retardant coating, providing initial fire protection and aesthetic effect; (2) a plurality of core layers: a nanocomposite material prepared by mixing the raw material components in (i) above as the core layer; (3) Several isolation layers: located between the core layers or between the core layer and the surface layer, made of nanoporous materials, used to isolate heat transfer and flame penetration; (III) Preparation method: Step 1: Preparation and pretreatment of core layer raw materials: Mix the basic nanomaterials, fire retardant enhancers, binders and additives in proportion and perform high-speed dispersion treatment to ensure that each component is evenly dispersed; Step 2: Core layer preparation: The pre-treated mixture is subjected to processes such as extrusion, injection molding or compression molding to form a preliminary core layer sheet; Step 3: Multi-layer structure construction: According to the design requirements, the core layer panels are stacked, and the isolation layer materials are added between the layers. The layers are tightly combined through hot pressing or vacuum pressing technology; Step 4: Surface treatment: spraying nano-level fire-retardant coating on the surface of the building material to produce the multi-level fire-retardant nano-composite building material.
2. The multi-level fireproof nanocomposite building material according to claim 1, characterized in that: The basic nano material in the core layer raw material component is a mixture of nano silicon dioxide and nano aluminum oxide, the nano silicon dioxide particle size is 10-30 nanometers, the nano aluminum oxide particle size is 20-60 nanometers, and the weight ratio is 1:1.5 to 1:2.
5.
3. The multi-level fireproof nanocomposite building material according to claim 1, characterized in that: The fireproof reinforcing agent in the raw material component of the core layer is a mixture of nano-scale intumescent flame retardant and nano-scale aluminum hydroxide, the particle size of which is less than 100 nanometers and the weight ratio is 1:0.8 to 1:1.
2.
4. The multi-level fireproof nanocomposite building material according to claim 1, characterized in that: The core layer raw material components: The polymer resin is epoxy resin or polyurethane resin, with a molecular weight of 2000-6000 and an addition amount of 10%-20%; The particle size of nanoclay is less than 50 nanometers, and the addition amount is 2%-5%; The dispersant is polycarboxylate, added in an amount of 0.5%-1.5%; The coupling agent is silane or titanate, and the addition amount is 0.5%-1.5%; The plasticizer is phthalate ester, and the added amount is 1%-3%.
5. The multi-level fireproof nano-composite building material according to claim 1, characterized in that: In step 1 of the preparation method: The high-speed dispersion processing speed is 3000-4000 rpm, the processing time is 20-25 minutes, and it is supplemented by ultrasonic dispersion.
6. The multi-level fireproof nano-composite building material according to claim 1, characterized in that: In step 2 of the preparation method: The molding process temperature is 150-170 degrees Celsius, the pressure is 10-15MPa, and it is naturally cooled to room temperature.
7. The multi-level fireproof nano-composite building material according to claim 1, characterized in that: In step three of the preparation method: The hot pressing or vacuum pressing temperature is 130-160 degrees Celsius, the pressure is 8-15MPa, and the holding time is 20-25 minutes.
8. The multi-level fireproof nano-composite building material according to claim 1, characterized in that: In step 4 of the preparation method: The selected fire retardant coating is sprayed with a thickness of 80-150 microns, sprayed and dried at least three times, and cooled naturally after each spraying.
9. The multi-level fireproof nano-composite building material according to claim 1, characterized in that: In the isolation layer of building material structure: The nanoporous material is nano-scale silica aerogel or nano-carbon foam, with a porosity of not less than 92%, a thermal conductivity of less than 0.015 W / (m·K), and a thickness of 2-4 mm.
10. The multi-level fireproof nano-composite building material according to claim 1, characterized in that: Fire retardant coatings used on the surface of building materials: Selected from acrylic fire retardant coating, epoxy resin fire retardant coating or polyurethane fire retardant coating, and its fire protection grade is not lower than B1 grade.